2019
DOI: 10.3390/ijms21010181
|View full text |Cite
|
Sign up to set email alerts
|

Intranasally Administered Human MSC-Derived Extracellular Vesicles Pervasively Incorporate into Neurons and Microglia in both Intact and Status Epilepticus Injured Forebrain

Abstract: Extracellular vesicles (EVs) derived from human bone marrow mesenchymal stem cells (hMSCs) have great promise as biologics to treat neurological and neurodegenerative conditions due to their robust antiinflammatory and neuroprotective properties. Besides, intranasal (IN) administration of EVs has caught much attention because the procedure is noninvasive, amenable for repetitive dispensation, and leads to a quick penetration of EVs into multiple regions of the forebrain. Nonetheless, it is unknown whether brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 55 publications
3
71
0
Order By: Relevance
“…IN administration of EVs has been tested in neurological disorders including Parkinson's disease 82 and status epilepticus (SE), both in pilocarpine‐induced 50 or kainate‐induced 83 models of SE, lipopolysaccharide (LPS)‐induced brain inflammation model, experimental autoimmune encephalomyelitis, GL26 tumor model, 84 and the autism BTBR T+tf/J (BTBR) mice model 85 . However, except for the LPS‐acute inflammatory model, 84 all these studies have exploited chronic EV treatment, with mice being sacrificed at the end of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IN administration of EVs has been tested in neurological disorders including Parkinson's disease 82 and status epilepticus (SE), both in pilocarpine‐induced 50 or kainate‐induced 83 models of SE, lipopolysaccharide (LPS)‐induced brain inflammation model, experimental autoimmune encephalomyelitis, GL26 tumor model, 84 and the autism BTBR T+tf/J (BTBR) mice model 85 . However, except for the LPS‐acute inflammatory model, 84 all these studies have exploited chronic EV treatment, with mice being sacrificed at the end of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The rats and mice (n = 2/species) were moderately anesthetized with a cocktail of ketamine, xylazine and acepromazine, and their nostrils were treated with 10 µl of hyaluronidase (Sigma-Aldrich, St. Louis, MO, USA) to enhance the permeability of the nasal mucous membrane. Thirty minutes later, labelled EVs were administered (150 × 10 9 [~75 µg]/rat and 25 × 10 9 [~12.5 µg]/mouse), as detailed in our recent report [22]. Six hours later, the animals were perfused, the brain tissues were processed for cryostat sectioning, and thirty-micrometre-thick coronal sections through the entire forebrain, midbrain and hindbrain, were collected serially.…”
Section: Tracking Of Hipsc-nsc Evs In the Adult Rat And Mouse Brain Fmentioning
confidence: 99%
“…Six hours later, the animals were perfused, the brain tissues were processed for cryostat sectioning, and thirty-micrometre-thick coronal sections through the entire forebrain, midbrain and hindbrain, were collected serially. Serial sections through the entire brain were selected and processed for immunofluorescent staining using appropriate primary antibodies against NeuN (1:1000; Millipore), IBA-1 (1:1000; Abcam), GFAP (1:3000; Dako, Glostrup, Denmark), S-100β (1:1000; Sigma) and calbindin (1:500; Sigma), as described in our previous report [22]. The sections were examined using Z-section analysis in a confocal microscope for the distribution of EVs in different cell types (neurons, microglia and astrocytes) in multiple regions of the brain.…”
Section: Tracking Of Hipsc-nsc Evs In the Adult Rat And Mouse Brain Fmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar process likely also aids the quick entry of nanosized EVs into the brain when administered intranasally. Recent studies have shown that intranasally administered stem cell-derived EVs permeate the entire forebrain and incorporate into different neural cells within 6 hours [49,50]. Such rapid targeting by EVs is likely due to their quick entry into the subarachnoid space through perineurial spaces around olfactory nerves passing through the cribriform plate and subsequent transportation through CSF flow into the ISF.…”
Section: Relationship Between the Isf Csf And The Bloodbrain Barriermentioning
confidence: 99%